Investigating the Efficacy of an Herbal Spray, Immuno Plus, in Mitigating Ulceration: Insights from a Rat Model Study - Chimthanawala, Yusuf; Chimthanawala, Nasreen; Khan, Shagufta; Padhare, Shilpa; Kediya, Ankit (Jordan Journal of Pharmaceutical Sciences, 2026)
Treatment for recurrent aphthous ulceration (RAS) is challenging. Immuno Plus spray, which contains Aspidosperma (10% v/v), Ocimum sanctum (20% v/v), Curcuma longa (20% v/v), Tinospora cardifolia (20% v/v), Echinacea angustifolia (20% v/v), and Azadirachta indica (10% v/v) was evaluated for its anti-ulcer activity. Ulcer was induced with acetic acid in fifty-four Wistar albino rats that were divided into nine groups. Treatment began on the third day, once the ulcers had clearly developed. One group served as a control and received no treatment, while the other groups were treated with either individual extracts, Immuno Plus, or a marketed formulation. By day 7, the control group still exhibited disrupted epithelium, whereas re-epithelization and healing were observed in the groups treated with Immuno Plus and the marketed formulation. There was minimal reduction in ulcer size in groups treated with the individual extracts at the same dosage, compared to the Immuno Plus group, which contained a mixture of all the extracts. The spray demonstrated synergistic effects, addressing various aspects of ulcer formation and healing.